2022
DOI: 10.34172/bi.2022.23266
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and probable lung cancer risk

Abstract: The pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global crisis with a growing number of mortalities and morbidities worldwide. Despite performing numerous researches, there are still considerable unrevealed details regarding the long-term complications and post-infection immunity of the coronavirus disease 2019 (COVID-19). Based on pathophysiological features, SARS-CoV-2 may act similarly as an oncovirus in the lung. This letter summarized three possible oncogenic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“… 35 , 36 Pulmonary fibrosis may be a long-term complication of coronavirus-infected patients, which increases the risk for the development of lung cancer. 37 Increasing risk of long-term pulmonary complications was also observed in survivors of SARS-CoV-2 infection. However, methods for directly detecting latent virion in pulmonary tissue are very few.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 35 , 36 Pulmonary fibrosis may be a long-term complication of coronavirus-infected patients, which increases the risk for the development of lung cancer. 37 Increasing risk of long-term pulmonary complications was also observed in survivors of SARS-CoV-2 infection. However, methods for directly detecting latent virion in pulmonary tissue are very few.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, these methods are very effective and easy to use, as PET screening is not required. However, previous studies have reported long-term lung complications in patients infected with SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV). , Pulmonary fibrosis may be a long-term complication of coronavirus-infected patients, which increases the risk for the development of lung cancer . Increasing risk of long-term pulmonary complications was also observed in survivors of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Low ACE2 levels contribute to malignancies and poor prognostic cancers. 127 A comprehensive bioinformatic and systemic biological analysis identified 122 COVID-19/NSCLC interactional genes and 21 interactional hub genes. The enrichment analysis revealed common signaling pathways between COVID-19 and NSCLC.…”
Section: Lung Cancermentioning
confidence: 99%
“…Also, in NSCLC, downregulation of ACE2 was found to occur after COVID‐19 infection. Low ACE2 levels contribute to malignancies and poor prognostic cancers 127 . A comprehensive bioinformatic and systemic biological analysis identified 122 COVID‐19/NSCLC interactional genes and 21 interactional hub genes.…”
Section: Unveiling the Lethal Convergence: Exploring The Intersection...mentioning
confidence: 99%
“…The key environmental types of biological pollutants include biological allergens (e.g., cat/dog dander and saliva, house dust mites, cockroaches, molds, and pollen) and microorganisms (viruses and bacteria) [ 14 ]. Several studies have shown that pathogenic microorganisms such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 15 , 16 ], human immunodeficiency virus (HIV) [ 17 ], human papillomavirus (HPV) [ 18 ], Epstein–Barr virus (EBV) [ 19 ], Helicobacter pylori ( H. pylori ) [ 20 ], Streptococcus pneumoniae ( S. pneumoniae ) [ 21 ], Mycobacterium tuberculosis ( M.tb ) [ 22 ], Chlamydia pneumoniae ( C. pneumoniae ) [ 23 ], and the common allergen house dust mite [ 24 ] are strongly associated with lung cancer. However, few studies have linked these pathogens/allergens to biological pollutants, and the concept of biological pollutants seems to be partially neglected in research on environmental pollutants and lung cancer, despite the extensive research into air pollution and lung cancer.…”
Section: Introductionmentioning
confidence: 99%